On the early stages of precipitation during direct ageing of Alloy 718. (15th April 2020) - Theska, F.; Nomoto, K.; Godor, F.; Oberwinkler, B.; Stanojevic, A.; Ringer, S.P.; Primig, S.
Abstract: The Ni-based superalloy Alloy 718 is used in aircraft engines as high-pressure turbine discs and must endure challenging demands on high-temperature yield strength, creep-, and oxidation-resistance. Nanoscale γ′- and γ″-precipitates commonly found in duplet and triplet co-precipitate morphologies provide high-temperature strength under these harsh operating conditions. 'Direct ageing' of Alloy 718 is an attractive alternative manufacturing route known to increase the yield strength at 650 °C by at least +10%, by both retaining high dislocation densities and changing the nanoscale co-precipitate morphology. However, the detailed nucleation and growth mechanisms of the duplet and triplet co-precipitate morphologies of γ′ and γ″ during the direct ageing process remain unknown. We provide a correlative high-resolution microscopy approach using transmission electron microscopy, high-angle annular dark-field imaging, and atom probe microscopy to reveal the early stages of precipitation during direct ageing of Alloy 718. Quantitative stereological analyses of the γ′- and γ″-precipitate dispersions as well as their chemical compositions have allowed us to propose a qualitative model of the microstructural evolution. It is shown that fine γ′- and γ″-precipitates nucleate homogeneously and grow coherently. However, γ″-precipitates also nucleate heterogeneously on dislocations and experience accelerated growth due to Nb pipe diffusion. Moreover, the co-precipitation reactions are largely influenced by solute availability and the potential for enrichment of Nb and rejection of Al+Ti. Graphical abstract: Image, graphical abstract